Efficient Equilibrium Concepts in Non-cooperative Network Formation - Panagopoulou, Panagiota N. (Algorithms, Probability, Networks, and Games, 2015)
We review here some recently proposed models of non-cooperative network creation games where the nodes of a network perform edge swaps in order to improve their communication costs. Our focus is on examining the structure of stable (equilibrium) networks that correspond to efficient notions of equilibria, in the sense that the nodes of the network are able to decide which links to add and which to remove in order to achieve a minimal cost, given the strategies of the other nodes. We also review results on the capability of the network nodes of converging into an equilibrium network by performing local selfish improvement steps.